1997
DOI: 10.1002/(sici)1096-9861(19970217)378:3<320::aid-cne2>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining for substance P receptor labels GABAergic cells with distinct termination patterns in the hippocampus

Abstract: A specific antiserum against substance P receptor (SPR) labels nonprincipal neurons in the cerebral cortex of the rat (T. Kaneko et al. [1994], Neuroscience 60:199-211; Y. Nakaya et al. [1994], J. Comp. Neurol. 347:249-274). In the present study, we aimed to identify the types of SPR-immunoreactive neurons in the hippocampus according to their content of neurochemical markers, which label interneuron populations with distinct termination patterns. Markers for perisomatic inhibitory cells, parvalbumin and chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 80 publications
5
46
0
Order By: Relevance
“…Morphological studies indicate that the hippocampal formation is richly innervated by axons containing SP (Borhegyi & Leranth, 1997). In addition, GABAergic neurons distributed in all hippocampal sub®elds possess SP receptors (Nakaya et al, 1994;Acsady et al, 1997). In an early work carried out in our laboratory, we found that SP and other peptides of the tachykinin family can powerfully excite rat hippocampal interneurons located in the CA1 region (Dreifuss & Raggenbass, 1986).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Morphological studies indicate that the hippocampal formation is richly innervated by axons containing SP (Borhegyi & Leranth, 1997). In addition, GABAergic neurons distributed in all hippocampal sub®elds possess SP receptors (Nakaya et al, 1994;Acsady et al, 1997). In an early work carried out in our laboratory, we found that SP and other peptides of the tachykinin family can powerfully excite rat hippocampal interneurons located in the CA1 region (Dreifuss & Raggenbass, 1986).…”
Section: Discussionmentioning
confidence: 83%
“…They were deemed to be interneurons if they responded to SP. Indeed, interneurons immunoreactive for SP receptors are distributed in all hippocampal sub®elds, whereas pyramidal cells appear to be devoid of SP receptor immunoreactivity (Nakaya et al, 1994;Acsady et al, 1997). In addition, we previously showed that a majority of nonpyramidal neurons in stratum pyramidale, identi®ed on the basis of their characteristic response to orthodromic activation of Schaffer's collaterals, respond to SP by a reversible, concentrationrelated increase in ®ring (Dreifuss & Raggenbass, 1986).…”
Section: Effect Of Tgot On Ca1 Interneuronsmentioning
confidence: 99%
“…1 Nonetheless, the complexity of hippocampal cellular architecture and neuronal connectivity may allow fluctuations in gene expression in one subregion to induce cellular and morphologic alterations in neighboring sublayers. However, current findings provide additional evidence that BDNF and NK-1 receptors are involved in pain-or stress-evoked plastic changes in the CNS, particularly within the limbic system.…”
Section: Discussionmentioning
confidence: 99%
“…The co-expression of SP receptors and PV has previously been reported for the dentate, CA1, and CA3 subregions of the dorsal HPC (Acsady et al, 1997; Sloviter et al, 2001) and alterations in the co-expression has been used to quantify changes in HPC interneuron number in animal models of epilepsy (Sloviter, 1991; Sloviter et al, 2001; Sloviter et al, 2003), in that substance P receptors are continuously expressed even when activity-dependent PV content is lost. Verifying the extent of PV-expressing interneuron cell survival by measuring the co-expression of SP and PV in the HPC in the MAM model would be consistent with the pathological findings reported in schizophrenia patients.…”
Section: Introductionmentioning
confidence: 95%